The service offered by a third-party company in the execution of a cycling trip - Silva, Natalya Reis da; Oliveira, Oliveira; Gonçalves, Wellington; Ghirotti, Gabryela Martins; Rocha, Alessandro Roberto da (Brazilian Journal of Production Engineering, 2022)
The operational processes and the travel experience are fundamental to the tourist's satisfaction. In order to optimize their services, it is common for companies to outsource a certain activity, but this process must be done technically. The case described in this paper is about an operator that hired a carrier to transfer a group of cyclists and their bicycles to and from a destination. In the return trip, the bicycles were loaded on the van, but the blocking of José's bicycle (pseudonym) was not correctly done by the carrier, resulting in material and emotional damage to the people involved. Thus, by means of documentary and bibliographical research and data collection, the objective of this study was to describe and analyze the aforementioned case from an operational point of view, from three points of view: criteria for the choice of suppliers; parameters for monitoring and evaluating the supplier's service; and support after the provision of the service. The results showed the importance of establishing criteria for selecting suppliers and the need for support to the consumer after the sale. Furthermore, negligence on the part of the operator and imprudence and negligence on the part of the carrier were verified.
Keywords: Cycling; outsourcing; human failure